EXPENSE AND ACCOUNTING CONCEPTS AND STANDARDS. - Miller, Hermann C. (The Accounting Review, 1949)
Abstract It is always difficult to disagree with the logic of an argument presented by Professor W. A. Paton. His article published in the January 1949, issue of the journal "The Accounting Review," presents a devastating barrage of reductio ad absurdum, invective, and fascinating wit, which may too readily be accepted by his readers. The issues at stake should be drawn dearly. Irrelevant comments and argument based upon false assumptions should be discarded before there is any disposition to repudiate the statement, Accounting Concepts and Standards Underlying Corporate Financial Statements. It should not be assumed that because of insistence upon the use of recorded cost as the only available objective information there is any suggestion of belief in or advocacy for the proposition that careful consideration should not be given to important changes such as may be found in price level changes and many other considerations. However, such considerations lie wholly beyond and outside of the area of basic corporate financial statements and at the same time may be said to lie within the area of managerial judgment, investment analysis, and interpretation. In the latter area, it is to be assumed that the accountant of integrity, competence and social responsibility may make a valuable contribution.